Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV SONNE during cruise SO180 - Udo Barckhausen; Willi Weinrebe (PANGAEA, 2025)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was almost continuously recorded during RV SONNE cruise SO180. Data was recorded on 27 days between 2004-11-08 and 2004-12-04. This dataset contains a transit survey in the South Pacific Ocean with nine parallel survey lines north of the Gallego Rise and three survey lines on the continental shelf of Chile. The approximate average depth of the entire dataset is around 4200m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus SVP files are added to this dataset. However, data analysis of the multibeam raw data revealed that SVP has never been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress et al., 2024).